An Approach towards the Measurement of Nanometer Range Distances Based on Cu2+ Ions and ESR - Yang, Zhongyu; Kise, Drew; Saxena, Sunil (The journal of physical chemistry. B, 2010)
We present the measurement of Cu2+−Cu2+ and Cu2+−nitroxide distance distributions using double electron−electron resonance (DEER) on a proline-based peptide and an alanine-based peptide. The proline-based peptide contains two well-characterized Cu2+ binding segments, PHGGGW, separated by seven proline residues. The alanine-based peptide contains a PHGGGW segment at one end of the peptide and a nitroxide spin label attached to a cysteine residue close to the other end of the peptide. DEER experiments were performed at several external magnetic fields and resonance offsets to probe the orientational effects on the Cu2+-based DEER signal. Subtle but detectable orientational effects were observed from the DEER spectra of both peptides. A general theoretical model was developed to analyze the experimental data sets. We show that the Tikhonov regularization-based method is not applicable to extract precise Cu2+-based distance distributions. Instead, a full data analysis is required to obtain the distance distributions and relative orientations between spin centers. A 30 Å mean Cu2+−Cu2+ distance and a 27 Å mean Cu2+−nitroxide distance were determined in the two peptides. These distances are consistent with structural models and with earlier measurements. Constraints on the relative orientation between paramagnetic centers in these two model peptides were determined by examination of the orientational effects. The data analysis procedure is system independent, and therefore is applicable to more complicated biological systems.